Identification of small-molecule ion channel modulators in C. elegans channelopathy models - Qiang Jiang (Nature Portfolio, 2018)
Mutations in the voltage-gated K+ channel human ether-a-go-go-related gene (hERG) lead to Long-QT syndrome, causing life-threatening cardiac arrhythmia. Here the authors use C. elegans as a platform to run a channelopathy drug screen, identifying drugs to target hERG mutants.